Eye Glance Behavior Associated with Cell-Phone Use: Examination with Naturalistic Driving Data. (September 2014) - Bao, Shan; Flannagan, Carol; Xiong, Huimin; Sayer, Jim
The purpose of this study is to examine eye-glance patterns of drivers engaged in cell phone related tasks. To observe eye-glance patterns, researchers used naturalistic driving data from the Integrated Vehicle-Based Safety Systems field operational test to construct and tabulate two datasets. One dataset included gaze data that were coded from cell phone conversation clips by fifty different drivers under different driving conditions. The second dataset was created in a similar way using video clips from twenty-four drivers who engaged in visual-manual tasks (e.g., texting and dialing). Mixed-model analyses were conducted. Results showed that drivers' on-road gazes were longer when they were engaged in a cell phone conversation than when they were not engaged. Off-road gaze length was the same, regardless of task involvement. In contrast, drivers who engaged in visual-manual tasks had substantially shorter on-road gaze length compared to when those same drivers were not involved in visual-manual tasks.